Strategies for Parent Involvement During Distance Learning in Arabic Lessons in Elementary Schools - Amanda Kartel; Malcolm Charles; Hilsheimer Xiao; Debasish Sundi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
This study aims to find various obstacles, describe, and provide strategies for parents when accompanying and providing direction to their children in distance learning. The method used in this research is the interview method. Interview, observation, listening, and note-taking techniques are data collection techniques used. The results of this study indicate that there are barriers for parents in distance learning. Among them are difficult internet signals, expensive internet quotas, and parents who are not able to fully guide and understand the material, so you have to ask your friends directly. The role of parents is very conducive to the academic success of a child. Always encourage and have innovations in child supervision so that children do not feel bored or even stressed in learning. There needs to be smooth coordination between parents and teachers. This assessment is needed to improve student learning outcomes. In the application of the home learning system, parents play an important role in the student learning process in the distance learning process at home today.